2018
DOI: 10.1371/journal.pone.0195210
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ischemic stroke in metabolically healthy obesity: A nationwide population-based study

Abstract: BackgroundWhether metabolically healthy obese (MHO) individuals are at increased risk of ischemic stroke is not well known. We investigated the association of the MHO phenotype with ischemic stroke.MethodsA total of 354,083 adults (age 45.8 ± 14.2 years) from the Korean National Health Insurance Service–National Sample Cohort enrolled in 2004–2008 were followed-up for incident ischemic stroke until 2013. Subjects meeting none of the metabolic syndrome criteria were classified as ‘metabolically healthy’. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 37 publications
6
56
2
2
Order By: Relevance
“…Because various CVD outcomes are studied as composite outcomes, it is possible that obesity and metabolic health may have different associations with those outcomes, leading to heterogeneous results. Consistent with this statement, MHO was associated with atrial fibrillation but not with ischemic stroke when investigators used the same cohort to study these associations separately . In addition, the use of various MetS components to define metabolic health, which may or may not increase the cardiometabolic risk, could have also led to inconsistencies .…”
Section: Discussionmentioning
confidence: 93%
“…Because various CVD outcomes are studied as composite outcomes, it is possible that obesity and metabolic health may have different associations with those outcomes, leading to heterogeneous results. Consistent with this statement, MHO was associated with atrial fibrillation but not with ischemic stroke when investigators used the same cohort to study these associations separately . In addition, the use of various MetS components to define metabolic health, which may or may not increase the cardiometabolic risk, could have also led to inconsistencies .…”
Section: Discussionmentioning
confidence: 93%
“…The NHIS provides various medical information of the Korean population over the past decades, including inpatient and outpatient records of diagnostic codes, procedures, examinations including imaging studies, medication prescriptions, and demographic information of patients. Recently, public access to the NHIS database has been available, which enabled many researchers to apply the population-based analysis in various study fields including epidemiology, economics, environmental policy and industry and public health and medicine [6][7][8][9][10]. In a population-based analysis, diagnostic codes of the disease based on the International Classification of Diseases (ICD) code is used to identify clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Korea, as the record of the diagnosis is cumulatively stored in the claims database, it is hard to differentiate true clinical events from previous records based on diagnostic codes. In this regard, most of the population-based studies in Korea had focused on primary prevention of the disease by excluding patients with previous diagnosis of the study outcome [6][7][8][9][10]. Previously, several studies had attempted to evaluate the validity of primary diagnostic codes in nationwide claims based on its higher association with true clinical events [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and metaanalysis covering 50 studies revealed the prevalence of depression among stroke survivors to be 29% (95% confidence interval (CI) 25-32) [13]. In another meta-analysis covering 61 observational studies, the pooled frequency estimate of poststroke depression (PSD) was 31% (95% CI [28][29][30][31][32][33][34][35], though the proportional frequency varies across studies [14]. Moreover, in women, a prior history of depression and major physical disability was a significant predictor of PSD occurring within the first six months [15].…”
Section: Overview Of Cardio-cerebrovascular Ischemiamentioning
confidence: 99%
“…In summary, depression, a frequently occurring disease has a bidirectional relationship with ischemic CVD and partially shares common risk factors (such as obesity and diabetes) and mechanisms (such as inflammation and OS) with CVD, providing a new direction for future research. [32,33], and a nationwide population-based study concluded that obesity, especially the metabolically unhealthy type, raised the risk of stroke [34]. Besides ischemic stroke, obesity is considered as an independent risk factor for cardiovascular disease.…”
Section: Overview Of Depressionmentioning
confidence: 99%